Subungual hemangioma. - Milano, A. (European Journal of Pediatric Dermatology, 2017)
Hemangioma in the early days of life is not three-dimensional and is barely visible. It can appear as a flat red patch and this is the appearance most often reported by parents. Sometimes history and early physical examination point out a rounded or segmental ischemic and / or cyanotic patch or an ischemic patch with coarse telangiectasias inside it. The ischemic / cyanotic patch is probably the first manifestation of hemangioma, followed by neoangiogenesis with telangiectasias; the latter then converge to give a uniform red stain and finally the three-dimensional hemangioma (1, 2). However, many precursors remain flat in the stage of telangectasias in an ischemic halo or red, uniform spots. In our case, the diagnosis of hemangioma was confirmed, besides the history and the physical examination at the time of the first visit, also by the evolution in the following three years, expression of the hemangioma involution phase.